Integration of Building Information Modeling Adaptation for Industrialized Building System Projects - Logendiran, Chitrarasan; Abdul Rahim, Nur Soleha; Ibrahim, Fazdliel Aswad (Advanced and Sustainable Technologies (ASET), 2026)
This paper examines the integration of Building Information Modeling (BIM) adaptation into Industrialized Building System (IBS) projects to understand the current level of BIM adaptation and readiness among construction players, particularly IBS contractors, in WPKL and Selangor. It aims to evaluate the level of technological adaptation and the technology readiness index (TRI) for BIM-IBS projects and to uncover the relationship between technological adaptation and the TRI. Consequently, a comprehensive literature review and quantitative analysis were adopted to gather relevant information obtained through a questionnaire. The findings indicate a strong level of preparedness for BIM–IBS implementation across all aspects, with average scores typically ranging from 3.98 to 4.61. The financial readiness aspect achieves the highest average (M = 4.61, SD = 0.57). The normality test indicated a non-normal distribution; therefore, Spearman’s rank correlation was appropriate for this analysis. The results collectively show that all five factors financial, organizational, technical, individual, and sustainability, demonstrate significant positive correlations with the TRI. Despite certain variations, especially regarding organizational and financial factors, the general findings indicate a solid groundwork for effective BIM–IBS implementation, as long as governance, training, and strategic alignment are consistently enhanced.